PENGARUH APLIKASI MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL (SAVI) TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH KURIKULUM DAN PEMBELAJARAN DI UNIVERSITAS NEGERI PADANG - Rayendra Rayendra; Nofri Hendri; Septriyan Anugrah (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
This research is motivated by the low learning outcomes of students and lecturers have not invited students to be fully involved in the learning process. The lack of student understanding is caused because in general the learning process in the classroom is less interesting and tends to beteacher centered. This study aims to determine the effect of the application of the Somatic, Auditor, Visual, Intellectual (SAVI) Learning Model on Student Learning Outcomes in Curriculum and Learning Courses at UNP. This research uses a quantitative approach with adesign quasi-experimental. The study population was all students who took a course curriculum and learning in semester from January to June 2021 at a number of students 50 people, by taking sexy as a homogeneous sample class that is sexy 202110030019. Technique of sampling is purposive sampling, with the number of students at each each class is 25 people, where the average value of both classes is the same and is guided by the same lecturer. From the results of the study, the average value of the experimental class was higher than the control class, namely the experimental average of 81.28 while the average value of the group using conventional strategies was 73.2. Based on the t-test calculation, it is obtained that tcount > ttable is 4.019 > 1.677, withlevel of a 0.05 on df 48. Thus, it can be concluded that the application of the SAVI model has a significant effect on student learning outcomes in the Curriculum and Learning courses at UNP.Keywords: SAVI, Learning, Learning Outcomes